THE EFFECT OF INTERNET QUALITY CONNECTION AND AFTER SALES SERVICE TOWARDS CONSUMERS’ SATISFACTION AND ITS IMPLICATION ON CONSUMERS’ LOYALITY OF SATELLITE INTERNET PRODUCT MANGOESKY PT. TELKOMSAT - Sugianto, Nur; Arifin Sitio (Dinasti Publisher, 2020)
This study is aimed to analyze the effect of internet quality connection and after sales service towards consumers’ satisfaction and its implication on consumers’ loyalty of internet product MangoeSky Satellite PT. Telkomsat. The type of research used in this study is casual research. The population of this study is all permanent consumers of internet service MangoeSky satellite PT. Telkomsat, which is 4.108 subscribers. The determination of sample number was conducted by using slovin formula with the result that obtained 100 respondents. The analysis method used is the regression analysis test through SPSS version 25. The results of this study show that (1) Service quality has a positive and significant effect on consumers’ satisfaction, (2) After sales service has a positive and significant effect on consumers’ satisfaction, (3) Service quality has a positive and significant effect on consumers’ loyalty, (4) After sales service has a positive and significant effect on consumers’ loyalty, (5) Consumers’ satisfaction has a positive and significant effect on consumers’ loyalty, and (6) There is a positive indirect effect between service quality and after sales service for loyalty through consumers’ satisfaction, it means that consumers’ satisfaction can increase consumers’ loyalty.